THE ROLE OF THE PENSION INSURANCE SYSTEM IN THE FORMATION OF THE MODERN FINANCIAL SYSTEM OF UKRAINE - Rudyk, V.K. (The actual problems of regional economy development, 2019)
The questions of determining the role and place of the pension insurance system in the formation of the financial system of Ukraine, its influence on the development of the national economy are covered. Particular attention is paid to the study of the financial relationships of the national pension system with the main areas of the financial system of the state in the context of pension reform. The relationship of public finances with the pension insurance system is investigated, the main aspects of the impact of these two components of the financial system on each other are revealed. The new national pension legislation is analyzed, the role of the pension insurance system at the present stage of pension reform is noted. The evaluation of the formation and development of financial relations of the pension insurance system with the financial market, which is an important area of the financial system, is given. Attention is paid to the role of international financial institutions in the formation and development of national pension systems in European countries, their important legislative documents related to pension reform are analyzed. It is determined that at their initiative the main strategies, concepts, programs of development of national pension systems are being developed, taking into account the global risks posed to society. Attention is drawn to the priority of combined pension systems that combine state solidarity pension programs, as well as mandatory and voluntary savings. Ukraine also forms the type of national pension system that underpins the principles of pension insurance. It is substantiated that the financial potential of the pension insurance system will contribute to the development of the national economy of the country.